Blessed relative and ominous relative in heritage issues: A doctrinal study - Asham, Ammar Abdulhussein (Journal of Islamic Sciences, 2020)
There are some terms and concepts in the field of heritage that are vague and strange on one hand and controversial on the other hand. some of these terms are (kin, blessed and ominous). those terms are the core of this study and its main aim. By following induction methodology, the research will investigate these terms in some of the heritage problems and suggest juristic rules or regulations form them and solve the controversial objections upon these terms which may have unacceptable meanings from a juristic point of view. the researcher has concluded the following results: - There is no right to object the terms (blessed and ominous). - The blessed kin has a juristic rule to follow and the ominous also has one, their heritage problems come under there rules. - Those problematic terms have no influence on the statistics of the heritage, but they are regarded as a way or a means that help to understand and decide the right of the granddaughter (the son’s daughter) and the aunt (the father’s sister) in the cases of giving some of the heritage to the others.